An Overview of the Involvement of D-Serine in Cognitive Impairment in Normal Aging and Dementia - Orzylowski, Magdalena; Fujiwara, Esther; Mousseau, Darrell D.; Baker, Glen B. (Frontiers in Psychiatry, 2021)
Dementia, of which Alzheimer’s disease (AD) is the most common form, is characterized by progressive cognitive deterioration, including profound memory loss, which affects functioning in many aspects of life. Although cognitive deterioration is relatively common in aging and aging is a risk factor for AD, the condition is not necessarily a part of the aging process. The N-methyl-D-aspartate glutamate receptor (NMDAR) and its co-agonist D-serine are currently of great interest as potential important contributors to cognitive function in normal aging and dementia. D-Serine is necessary for activation of the NMDAR and in maintenance of long-term potentiation (LTP) and is involved in brain development, neuronal connectivity, synaptic plasticity and regulation of learning and memory. In this paper, we review evidence, from both preclinical and human studies, on the involvement of D-serine (and the enzymes involved in its metabolism) in regulation of cognition. Potential mechanisms of action of D-serine are discussed in the context of normal aging and in dementia, as is the potential for using D-serine as a potential biomarker and/or therapeutic agent in dementia. Although there is some controversy in the literature, it has been proposed that in normal aging there is decreased expression of serine racemase and decreased levels of D-serine and down-regulation of NMDARs, resulting in impaired synaptic plasticity and deficits in learning and memory. In contrast, in AD there appears to be activation of serine racemase, increased levels of D-serine and overstimulation of NMDARs, resulting in cytotoxicity, synaptic deficits, and dementia.